Accountability of a Person Possessing, Controlling or Providing Types of Drugs not from Plants with the use of Restorative Justice (a Case Study of the Cassation Decision number 1423K/PID.SUS/2016) - Aditia Johan Permana; Yusuf Muhamad Said (IHSA Institute, 2022)
Narcotics crime is an extraordinary crime. Therefore, the handling must also be extraordinary, not only using Law No. 35 of 2009 concerning Narcotics, but also the Criminal Code and the Crime of Money Laundering (TPPU). BNN until March 2021 had confiscated 3,462.75 kilograms of marijuana evidence, an increase of 143.64 percent compared to 2,410 kilograms of evidence in 2020, even though in a pandemic condition, covid 19 drug trafficking has increased marked by an increase in evidence confiscated in the context of enforcement. law. Thus, the condition of the pandemic and the consequences of working from home, the circulation of narcotics and the like rose, especially the type of marijuana. BNN asks for support from all parties to jointly support the eradication of these prohibited items. The research method is carried out in a normative juridical manner, which relies on literacy from various books, journals, expert opinions and is equipped with State Court Decisions to Cassation Decisions Against cases of handling illegal drug trafficking, class I. All are analyzed and made a narration so that it can be concluded in a study. In conclusion, the handling of drug crimes, in Indonesia still uses positive legal parameters, the aspect of imprisonment is not yet related to the aspect of restorative justice, it is not easy because there are no binding statutory regulations, except for regulations under the law other than the impact of drugs can damage the order. socially and economically to the potential to lose the best generation of the nation.